Efektivitas Pelayanan E-KTP melalui Sistem Jemput Bola (Sijebol) pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gianyar - Mariani, Desy; Supriliyani, Ni Wayan; Wijaya, Komang Adi Sastra (Socio-political Communication and Policy Review, 2025)
This study aims to determine the Effectiveness of e-KTP Services Through the Pick-up Ball System (Sijebol) at the Population and Civil Registration Service of Gianyar Regency. The research method used is descriptive qualitative. Informants in the study were selected using purposive and snowball techniques. Data were collected through observation, interviews, and documentation then analyzed using the Miles and Huberman model. The problem assessment used Duncan’s program effectiveness theory in Steers. The results of the study show that the effectiveness of e-KTP services through the Pick-up Ball System (Sijebol) at the Population and Civil Registration Service of Gianyar Regency is effective in increasing ownership of population documents, then seen from the indicators of goal achievement, integration, and adaptation, it has been running quite well, but is the integration indicator, especially the socialization process, it has not run optimally because the implementation of socialization is less effective and the community is less responsive so that information about services is not optimal. The policy recommendations offered are in the from of the need to increase cooperation in socialization between the regional government and the village, direct supervision, and procurement of facilities and infrastructure. Keywords : Service Effectiveness, e-KTP Service, Pick-up Ball System (Sijebol) Abstrak Penelitian ini bertujuan untuk mengevaluasi Efektivitas Pelayanan e-KTP Melalui Sistem Jemput Bola (Sijebol) pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gianyar. Dalam penelitian ini, metode yang digunakan adalah deskriptif kualitatif. Informan dalam penelitian dipilih menggunakan teknik purposive dan snowball. Data dikumpulkan melalui metode observasi, wawancara, dan dokumentasi kemudian dianalisis dengan model Miles and Huberman. Pengkajian masalah menggunakan teori efektivitas program dari Duncan dalam Steers. Hasil penelitian menunjukkan bahwa pelayanan e-KTP melalui Sistem Jemput Bola (Sijebol) pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gianyar terbukti efektif dalam meningkatkan kepemilikan dokumen kependudukan kemudian ditinjau dari indikator pencapaian tujuan, integrasi, dan adaptasi sudah berjalan cukup baik, tetapi dalam indikator integrasi khususnya proses sosialisasi belum berjalan secara optimal karena pelaksanaan sosialisasi kurang efektif dan masyarakat kurang responsive sehingga informasi tentang pelayanan belum maksimal. Rekomendasi kebijakan yang ditawarkan berupa perlu peningkatan kerjasama sosialisasi antara pemerintah daerah dengan desa, pengadaan pengawasan secara langsung, dan pengadaan sarana maupun prasarana. Kata Kunci : Efektivitas Pelayanan, Pelayanan e-KTP, Sistem Jemput Bola (Sijebol)